An economic perspective on Malawi's medical "brain drain" - Mohiddin Abdu; Record Richard (BMC, 2006)
Abstract Background The medical "brain drain" has been described as rich countries "looting" doctors and nurses from developing countries undermining their health systems and public health. However this "brain-drain" might also be seen as a success in the training and "export" of health professionals and the benefits this provides. This paper illustrates the arguments and possible policy options by focusing on the situation in one of the poorest countries in the world, Malawi. Discussion Many see this "brain drain" of medical staff as wrong with developed countries exploiting poorer ones. The effects are considerable with Malawi facing high vacancy rates in its public health system, and with migration threatening to outstrip training despite efforts to improve pay and conditions. This shortage of staff has made it more challenging for Malawi to deliver on its Essential Health Package and to absorb new international health funding. Yet, without any policy effort Malawi has been able to demonstrate its global competitiveness in the training ("production") of skilled health professionals. Remittances from migration are a large and growing source of foreign exchange for poor countries and tend to go directly to households. Whilst the data for Malawi is limited, studies from other poor countries demonstrate the power of remittances in significantly reducing poverty. Malawi can benefit from the export of health professionals provided there is a resolution of the situation whereby the state pays for training and the benefits are gained by the individual professional working abroad. Solutions include migrating staff paying back training costs, or rich host governments remitting part of a tax (e.g. income or national insurance) to the Malawi government. These schemes would allow Malawi to scale up training of health professionals for local needs and to work abroad. Summary There is concern about the negative impacts of the medical "brain-drain". However a closer look at the evidence for and against the medical "brain-drain" in Malawi suggests that there are potential gains in managing medical migration to produce outcomes that are beneficial to individuals, households and the country. Finally we present several policy options.